Current Status of Emerging PV Technologies: A Comparative Study of Dye-Sensitized, Organic, and Perovskite Solar Cells - Myrsini Giannouli (International Journal of Photoenergy)
The imminent depletion of conventional energy sources has motivated the advancement of renewable energy technologies. Third-generation photovoltaic technologies, such as dye-sensitized solar cells (DSSCs), organic solar cells (OSCs), and perovskite solar cells (PSCs), are being developed as alternatives to silicon solar cells. In recent years, there has been considerable interest in the market development of these emerging photovoltaic technologies, especially for sustainable solar energy applications. However, these technologies have not yet reached the maturity required for large-scale commercialization. Further research is required in order to improve the efficiency and stability of these devices, while keeping their production costs to a minimum. In this study, a comparative assessment of DSSCs, OSCs, and PSCs is conducted and the current state of the art of these promising technologies is investigated. Advanced techniques and research trends are examined from the perspective of novel materials, device modelling, and innovative device structures. The comparative advantages and limitations of each of these photovoltaic technologies are assessed in terms of device efficiency, durability, ease of fabrication, and performance-price ratio. Emphasis is placed on assessing the potential of these solar cell technologies for sustainable solar energy applications. Finally, the future outlook of these technologies is featured, and avenues for progress beyond the state of the art are explored.